O protocolo de morte encefálica na formação médica : um estudo nas escolas médicas do Paraná - Dibo, Fernando Henrique Almada (2014)
The concept of death has been undergoing changes over time. The technological advancement in the medical field therefore become obsolete the traditional clinical death definition, even if brain death occurs. Although, it has been a current subject, there are few available researches about brain death (BD) and about its clinical diagnostic protocol during the whole process of Medical Academic training. For this reason, the aim of this study was to evaluate students' knowledge about brain death and its clinical protocol, at Medical Schools of Paraná State. An observational, cross-sectional, descriptive research method was carried out with students from public and private Medical Schools. The investigation subjects were students from 5th and 6th grades of Medical schools who answered to a questionnaire with 22 questions about this survey's theme. Descriptive analysis was performed for all variables as well bivariate one through Chi-squared distribution, by Statistica 8.0 application. Trial results were considered significant for (p <0.05). Among 06 Universities from Paraná State, 635 students answered the questionnaire. Results have pointed out: 15.7% of subjects presented adequate knowledge about BD Protocol, if the subject obtained a performance equal to or superior to 75% of hits in the evaluation. It has also revealed statistically significant if the relationship between 6th year students and their knowledge about BD (p <0.01); the significant relationship between the option of stopping life support devices and students of 6th grade (p <0.01); from Public Medical Academic Schools (p <0.01); members of "other" religions (p <0 01). And showed that 84,2% of students at Medical Colleges are not comfortable to apply the BD clinical protocol. The analysis concluded that most of Medical Academic students presented lack of knowledge prevalence about Brain Death (BD) clinical protocol.